FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - RAHMAN PURA (AkMen JURNAL ILMIAH, 2021)
The research objective was to measure the effect of internal control systems, accounting information systems and financial controls on the quality of regional financial reports. The population of the study was the officials of the Jeneponto Regency Regional Apparatus Organization. Sampling using saturated sampling technique so that the number of samples and respondents at the same time as many as 43 officials. The data were collected using a questionnaire technique and the number of questionnaires distributed to respondents was 43 questionnaires. Data were analyzed using the SPSS application and analyzed using multiple regression analysis. The results showed that the internal control system and financial supervision had a positive and significant effect on the quality of financial reports, while the accounting information system had a positive and insignificant effect on the quality of financial reports. This research has implications for the efforts to increase the BPK RI audit opinion on the financial statements of the Jeneponto Regency Government from the Unqualified Opinion to the Unqualified Opinion.